Exploiting Benzophenone Photoreactivity To Probe the Phospholipid Environment and Insertion Depth of the Cell‐Penetrating Peptide Penetratin in Model Membranes. Issue 28 (6th June 2017) - Jiao, Chen‐Yu; Sachon, Emmanuelle; Alves, Isabel D.; Chassaing, Gérard; Bolbach, Gérard; Sagan, Sandrine
Abstract: Penetratin (RQIKIWFQNRRMKWKK) enters cells by different mechanisms, including membrane translocation, thus implying that the peptide interacts with the lipid bilayer. Penetratin also crosses the membrane of artificial vesicles, depending on their phospholipid content. To evaluate the phospholipid preference of penetratin, as the first step of translocation, we exploited the benzophenone triplet kinetics of hydrogen abstraction, which is slower for secondary than for allylic hydrogen atoms. By using multilamellar vesicles of varying phospholipid content, we identified and characterized the cross‐linked products by MALDI‐TOF mass spectrometry. Penetratin showed a preference for negatively charged (vs. zwitterionic) polar heads, and for unsaturated (vs. saturated) and short (vs. long) saturated phospholipids. Our study highlights the potential of using benzophenone to probe the environment and insertion depth of membranotropic peptides in membranes. Abstract : Fathoming the depths : Evidence for the direct interaction of the cell‐penetrating peptide penetratin with specific phospholipids was obtained by a photolabeling strategy (see picture). The method exploits the benzophenone triplet kinetics of hydrogen abstraction, which is faster for allylic hydrogen atoms. Benzophenone‐modified penetratin analogues were found to interact preferentially with phospholipids in disordered membrane domains.